Bridging the length scales between lithographic patterning and self assembly mechanisms in fabrication of semiconductor nanostructure arrays - Hull, Robert; Floro, J A; Gherasimova, M; Graham, J; Gray, J L; Portavoce, A; Ross, Frances M; Thorp, J (Journal of Physics: Conference Series, 2010)
We employ focused ion beam patterning of single crystal Si(100) surfaces to template the assembly of Ge(Si) nanostructure arrays. The evolution and final structures of the templated arrays are determined by combinations of transmission electron, low energy electron microscope, focused ion beam and scanning probe microscopies. It is shown how the positions of individual nanostructures may be controlled to the order of 10 nm. However, to achieve controlled spacings between elements that are in the 10 nm range requires careful matching of the characteristic lengths scales of self assembly mechanisms to the length scales of the external lithographic "forcing functions". © 2010 IOP Publishing Ltd.
4 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/048-366-191-463-372
Keywords: Assembly mechanism; Characteristic length; Electrons; Focused ion beams; Germanium; Ion beams; Lithographic patterning; Low energy electron microscopes; Nanostructure arrays; Nanostructures; Self assembly; Semiconductor nanostructures; Silicon wafers; Single crystal surfaces; Single crystals; Single-crystal Si; Transmission electron; dept.phy